Effect of calcium and magnesium on starch synthesis in maize kernels and its physiological driving mechanism - He, Zhaoquan; Shang, Xue; Zhang, Tonghui; Yun, Jianying (Frontiers in Plant Science, 2024)
The content of kernel starch (STC), which is a fundamental indicator of the nutritional value of maize, is directly correlated with the grain's taste and aroma. Both calcium (Ca) and magnesium (Mg) are critical nutrients that play a significant role in the growth and development of maize, as well as in the synthesis of STC. To determine the physiological driving mechanisms of Ca and Mg effects on the accumulation of STC synthesis in maize kernels and the characteristics of their effects on endogenous hormones and enzymes of STC synthesis in maize leaves, our study applied foliar Ca and Mg fertilizers at various levels to maize prior to pollination. (1) The levels of Ca, Mg, indole-3-acetic acid (IAA), gibberellin (GA), and zeatin riboside (ZR) in maize leaves increased and then decreased after the supplementation of Ca and Mg. They peaked on the 32nd day after pollination.In contrast, the levels of abscisic acid (ABA) initially decreased and then increased. Ca and Mg had a negative correlation with ABA and a positive correlation with IAA, GA, and ZR. (2) As the levels of Ca and Mg increased, correspondingly rose the activities of enzymes responsible for STC synthesis and the content of STC and its components. Principally influencing the synthesis of STC were ABA, IAA, uridine diphosphate-glucose pyrophosphorylase (UDPG), granule-bound starch synthase (GBSS), and soluble starch synthase (SSS). ( 3) "IAA-UDPG or GBSS-STC" was the predominant physiological regulation pathway of Ca on kernel STC, whereas "IAA-GBSS-STC" was the dominant physiological regulation pathway of Mg on kernel STC. The regulatory impact of STC by UDPG and GBSS was positive, as were the effects of IAA on UDPG and GBSS. In conclusion, the accumulation of kernel starch was significantly enhanced by Ca and Mg supplementation via the modulation of endogenous hormone levels and key enzyme activities. This research identifies a viable approach to improve the nutritional composition of maize.